PEMIKIRAN HISAB RUKYAH KLASIK (Studi Atas Pemikiran Muhammad Mas Manshur al-Batawi) - Ahmad Izzuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
Islamic teachings in Indonesia have been influenced by ulama, or Islamic thinkers from Saudi Arabia (Haramin). One of these Islamic teaching areas is rukyyahhisab. One of prominent Islamic teachings on rukyah was spread by Mas Manshur al-Batawi. While, his teaching, which was based on Ptolomeus' Geocentrics theory, was being put aside as the Geocentric theory itself and was replaced by Heliosentrics theory, interestingly, his teaching is still widely used in deciding the starting Qomariyah month by many muslim communities in Indonesia, including al-Khairiyah al-Manshuriyah Jakarta and Pondok Pesantren Ploso Mojo Kediri, East Java. Meanwhile, Mas Manshur al- Batawi admitted the existence of this loophole as well. Thus, I am interested in researching further on his Islamic thinking in this study.